The Contestation of Legal Foundations in the Resolution of Islamic Economic Disputes in Religious Courts - Hasanudin; Kamsi; Anshori, Ahmad Yani (Sharia Faculty of State Islamic University of Prof. K.H. Saifuddin Zuhri, Purwokerto, 2024)
Prior to the issuance of Supreme Court Regulation No. 2 of 2008, judges in Sharia economic dispute cases primarily relied on legal sources from kutub al-turāṡ (classical fiqh texts), including those pertaining to fiqh al-qadā’ (jurisprudence on adjudication). However, following the implementation of this regulation, some judges have continued to incorporate the Civil Code in their legal reasoning. This article seeks to examine the legal framework for resolving Sharia economic disputes in Indonesia. The theoretical foundation applied by the author is Lawrence Meir Friedman’s legal system theory. This study employs a normative legal approach to explore the legal system governing Sharia economic justice in Indonesia’s Religious Courts. It examines decisions from the Religious Courts in Purbalingga, Banyumas, and Purwokerto, focusing on rulings made both before and after the issuance of the Supreme Court Regulation on the Compilation of Sharia Economic Law (KHES), as well as five decisions from 2018-2019. The study’s findings reveal that the legal framework for Sharia economic dispute resolution in Indonesia has adequately addressed community needs, with the Religious Courts holding exclusive jurisdiction over these matters. However, there is an ongoing contestation between Islamic legal sources and civil law, which is rooted in Dutch law, in the decisions analyzed. Moreover, the absence of a Compilation of Islamic Economic Procedure Law based on Islamic Law has contributed to the suboptimal implementation of legal substance and culture. As a result, according to Friedman’s legal system theory, the legal framework for resolving Islamic economic disputes has not yet functioned effectively from the perspective of Islamic law.